THE ROLE OF ENGLISH THEATER AND CINEMA AS AUTHENTIC MATERIALS IN LANGUAGE TEACHING - Qobulova, Durdona; Inomjonova , Maxliyo Maxamadjon qizi; Raximova , I.B; To‘xtamatova , I (Educational Research in Universal Sciences, 2023)
Today, the need for a foreign language, especially English, is growing day by day. In particular, it is included in the 1st grade textbook in schools, and it is being taught to improve the enthusiasm of the young generation for the language. Cinema is of great importance in learning the language. Why is the expression "natural speaking" in English widely used in oral speech? widely improves the ability to speak like "natives". It also plays an important role in improving pronunciation. With the introduction of modern technology, the tradition of teaching English is changing significantly. This article is written about the appropriate use of modern technologies in learning and teaching English, and the teacher’s search for himself, feeling responsible, introducing innovations into the lessons, ensuring that the lesson is interesting and lively.